Drilling Performance of Micro-Textured Twist Drill Bit for Ti-6Al Alloy: Validated FEM and Statistical Approaches - Ozturk, Erkan; Kaya, Kadir (Elsevier Sci Ltd, 2024)
The titanium alloy, particularly Ti-6Al-4V, is an extensively demanded material in diverse sectors because of its superior physical and chemical properties. Nevertheless, the inherent hardness of the material causes challenges during machining operations. The alloy's heat-resistance characteristic induces increased friction and heat generation on cutting tools, ultimately causing a decrease in the tool life. In an attempt to overcome this issue, numerous forms of surface texturing have been investigated with the aim of improving the tribological characteristics of the material. The aim of the present investigation was to enhance the cutting performance of drill bits by implementing micro-textured patterns, hence minimizing thrust force, torque, and tool temperature. The combined effect of three distinct micro-textured geometries on a drill bit's flank, flute, and margin surfaces, with the influence of coating conditions, on the performance of drilling operations was investigated. The Finite Element Method (FEM) was used to perform a range of varied drilling operations. The Grey Relation Analysis (GRA) and General Linear Model (GLM) were employed to assess and compare the drilling performances with respect to thrust force, torque, and drill bit temperature. It was found that the square-sectioned textures on the side face exhibited the most obvious influence on the drilling performance. In the meantime, the textures found on the flute face were identified as having a comparatively smaller influence. The ideal configuration for the drill bit entailed a flank face with a square sectioned texture, a flute face without any texture, a margin face with a square sectioned texture, and a hard coating. As a result, the current situation substantially reduced cutting forces, tool wear, and tool temperature by 51 %, 20.5 %, and 23.4 % compared to the drilling condition without textured drill bits.
Kaya, Kadir/0000-0003-4273-6684
Keywords: Micro-Textured Drill Bit; Ti-6Al-4V; Finite Element Method; Grey Relation Analysis